Recovery of Recombinant Canine Distemper Virus That Expresses CPV-2a VP2: Uncovering the Mutation Profile of Recombinant Undergoing 50 Serial Passages In Vitro - Liu, Fuxiao; Lin, Jiahui; Wang, Qianqian; Zhang, Youming; Shan, Hu (Frontiers in Cellular and Infection Microbiology, 2022)
Canine distemper and canine parvoviral enteritis are caused by infections of canine distemper virus (CDV) and canine parvovirus type 2 (CPV-2), respectively. They are two common infectious diseases that cause high morbidity and mortality in affected dogs. Combination vaccines have been broadly used to protect dogs from infections of CDV, CPV-2 and other viruses. VP2 is the most abundant protein of CPV-2 capsid. It elicits potent immunity in animals, and therefore is widely used for designing subunit antigen-based vaccines. In this study, we rescued a recombinant CDV (QN vaccine strain) using reverse genetics. The recombinant CDV (rCDV-VP2) was demonstrated to express stably the VP2 in cells for at least 33 serial passages in vitro. Unfortunately, a nonsense mutation was initially identified in the VP2 open reading frame (ORF) at passage-34 (P34), and gradually became predominant in rCDV-VP2 quasispecies with passaging. Neither test strip detection nor indirect immunofluorescence assay demonstrated expression of the VP2 at P50. The P50 rCDV-VP2 was subjected to next-generation sequencing, which totally identified seventeen single-nucleotide variations (SNVs), including eleven transitions and six transversions. Out of seventeen SNVs, one and nine were identified as nonsense and missense mutations, respectively. Since the nonsense mutation arose in the VP2 ORF as early as P34, an earlier rCDV-VP2 progeny should be selected for vaccination of animals in the following experiment.